Circadian Clock Genes Regulate Temperature-Dependent Diapause Induction in Silkworm Bombyx mori - Homma, Satoshi; Murata, Akihisa; Ikegami, Masato; Kobayashi, Masakazu; Yamazaki, Maki; Ikeda, Kento; Daimon, Takaaki; Numata, Hideharu; Mizoguchi, Akira; Shiomi, Kunihiro (Frontiers in Physiology, 2022)
The bivoltine strain of the domestic silkworm Bombyx mori exhibits a facultative diapause phenotype that is determined by maternal environmental conditions during embryonic and larval development. Although a recent study implicated a circadian clock gene period (per) in circadian rhythms and photoperiod-induced diapause, the roles of other core feedback loop genes, including timeless (tim), Clock (Clk), cycle (cyc), and cryptochrome2 (cry2), have yet to be clarified. Therefore, the aim of this study was to elucidate the roles of circadian clock genes in temperature-dependent diapause induction. To achieve this, per, tim, Clk, cyc, and cry2 knockout (KO) mutants were generated, and the percentages of diapause and non-diapause eggs were determined. The results show that per, tim, Clk, cyc, and cry2 regulated temperature-induced diapause by acting upstream of cerebral γ-aminobutyric acid (GABA)ergic and diapause hormone signaling pathways. Moreover, the temporal expression of the clock genes in wild-type (wt) silkworms was significantly different from those of thermosensitive transient receptor potential ankyrin 1 (TRPA1) KO mutants during embryonic development. Overall, the findings of this study provide target genes for regulating temperature-dependent diapause induction in silkworms.